2015
DOI: 10.5755/j01.ee.26.4.6066
|View full text |Cite
|
Sign up to set email alerts
|

A Reference Model of Public Institutions’ Quality Practices, Citizens’ Satisfaction and Performance Quality

Abstract: In recent years improving public services quality by using quality management methods became one of the most important quality initiatives in Lithuanian public sector. Public institutions have a great challenge to ensure a high level quality focusing on the citizens' requirements, processes, innovation and environment as well. However, the relations of public institutions' quality dimensions do not receive a lot of attention from research community and practitioners. This paper complements Lithuanian public in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This situation has been much fierce recently as the competition moves to use social media to promise better products than their competitors (Alalwan et al, 2017) context is seen more appropriate under the context of producer-customer paradigm (Abdullah & Kalianan, 2008) However, the situation above occurs in a free market where competitors are available and have identical services. When a product or a service is monopolistically run by a producer especially by the government, a customer is different from a user (Daunorienė & Žekevičienė, 2015;Moodley, 2012). The need to represent the sovereign consumer is well in line with the democratic political philosophy where the individual is the supreme power repository.…”
Section: Citizen Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation has been much fierce recently as the competition moves to use social media to promise better products than their competitors (Alalwan et al, 2017) context is seen more appropriate under the context of producer-customer paradigm (Abdullah & Kalianan, 2008) However, the situation above occurs in a free market where competitors are available and have identical services. When a product or a service is monopolistically run by a producer especially by the government, a customer is different from a user (Daunorienė & Žekevičienė, 2015;Moodley, 2012). The need to represent the sovereign consumer is well in line with the democratic political philosophy where the individual is the supreme power repository.…”
Section: Citizen Satisfactionmentioning
confidence: 99%
“…It is almost certain that this is because the citizen has no option but using those services and products. In other words, the citizen's satisfaction would not be the concern of the government as no other options (Abdullah & Kalianan, 2008;Daunorienė & Žekevičienė, 2015).…”
Section: Citizen Satisfactionmentioning
confidence: 99%
“…Considering the above discussion and previous studies, Several studies have shown the effect of information quality on organizational performance through several organizational factors. These factors include service integration, user needs, human resources, and communications ( Alenezi et al., 2015 ), quality improvement ( Fotopoulos and Psomas, 2010 ), customer satisfaction of information system ( Daunoriene and Zekeviciene, 2015 ). The researchers are proposing the following hypothesis:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…IQ was most often described in an indirect relation, meaning that IQ affected organizational performance through other variables. This research was underpinned by variants of TAM or IS success models, where IQ typically affected usefulness/use and user satisfaction which in turn impacted organizational performance [10,15,31,46]. IQ was affecting organizational performance through several organizational factors, including user needs, service consolidation, communication, and human resources [6], customer satisfaction of IS [15], quality improvement [22], and management capabilities [50].…”
Section: Figure 5 Research Designmentioning
confidence: 99%